Gestión de recaudación de la empresa pública municipal de mercados, centros comerciales y bahías de Babahoyo - Cortez Macias, Leyber Daniel (2020)
This paper focuses on the study of the ability of the Municipal Public Company of Markets, Shopping Centers and Bay of Canton Babahoyo to obtain the estimated income from the rental of physical and permanent spaces in the different markets of Babahoyo, to cover their market operating and maintenance expenses. A study was carried out to identify the factors and conditions that cause MECECOB-EPB to be unable to meet the budgeted collection for a period, affecting its financial situation and causing liquidity problems for the institution. A series of tables was applied to demonstrate the differences between the items that should have been collected against those of the gender treasury, and to demonstrate the existing variations and try to explain why.